Visible learning for librarian teachers - Yu, Tiffany; Austin, Clayton; Faruquee, Murtaza; Smyth, Neil (Cambridge Scholars, 2020)
This chapter reports on an exploratory study which sought to examine the impact of visible learning pedagogies on student learning using a specific learning technology: Echo360. We identify research questions: how effective are activities for teachers and students in enabling the diagnosis of student learning before the classroom teaching? How effective are classroom teaching strategies based on the diagnosis identified? How effective are activities in enabling the assessment of impact on student learning after the classroom teaching? The project brings together three components to deliver a case study: the learning technology, Echo360; the visible learning framework; and the Library Research Skills Teaching. The study examines how librarian teachers used a specific technology to understand and evaluate their impact on student learning. A distinctive feature of this study is the role of students in classroom content creation. Students were employed to create activities before the “one-off” classroom experience.